Hepatic inflammatory pseudotumor mimicking malignancy: the value of differential diagnosis on contrast enhanced ultrasound. - Wen-Tao Kong; Wen-Ping Wang; Hai-Yun Shen; Hai-Yan Xue; Chun-Rui Liu; Dan-Qing Huang; Min Wu; Kong, Wen-Tao; Wang, Wen-Ping; Shen, Hai-Yun; Xue, Hai-Yan; Liu, Chun-Rui; et al. (Medical Ultrasonography, 2021)
The aim of this study is to investigate whether the use of contrast enhanced ultrasound (CEUS) can improve the differential diagnostic performance between hepatic inflammatory pseudotumor (HIPT) and other malignant tumors.Material and Methods: Forty-four patients with histological proven HIPTs were included in this retrospective study. The features of conventional ultrasound (US) and CEUS were evaluated.Results: Three kinds of enhanced pattern can be seen in the 44 nodules including homogeneous (n=18, 41%), heterogeneous (n=16, 36%) and rim-like enhancement (n=10, 23%). All of the nodules showed hypo-enhancement during the portal and delayed phase. The dominant nodules (n=29, 66%) presented wash-out within 60 s after contrast injection. Quick wash-in and wash-out was seen in 18 nodules (41%). Eighteen nodules (41%) were correctly diagnosed as HIPT, whereas the remaining 26 cases were misdiagnosed as malignancies (n=20, 45%) or with an uncertain diagnosis (n=6, 14%).Conclusion: CEUS was not enough to differentiate HIPT from hepatic malignancies, especially intrahepatic cholangiocarcinoma and liver metastasis. However, some CEUS imaging characteristics may be helpful for HIPT diagnosis.